Intravenous Acetylsalicylic Acid – Dose-Related Effects on Platelet Function and Fibrinolysis in Healthy Males - Husted, S E; Kristensen, S D; Vissinger, H; Mørn, B; Schmidt, E B; Nielsen, H K (Thrombosis and Haemostasis, 1992)
Low-dose acetylsalicylic acid (ASA) has been shown to be beneficial in patients with acute myocardial infarction and unstable angina pectoris. Oral administration of ASA is difficult in the acute phase of these syndromes. In this study we evaluated the effect of 25 mg, 50 mg or 100 mg of ASA given as an intravenous bolus injection on platelet function and fibrinolysis in healthy males and related this to plasma concentrations of ASA. No adverse effects were found. A complete inhibition of serum thromboxane B2 synthesis was demonstrated 5 min after injection of 100 mg ASA intravenously. ASA disappeared from the circulation within 60 min after bolus injection and at this time thromboxane B2 synthesis was inhibited dose-dependently by 71%, 90% and 100% for doses of 25 mg, 50 mg and 100 mg, respectively. Inhibition of thromboxane B2 synthesis after 100 mg of intravenous ASA was still 96.5% at 24 h and 93.4% at 48 h after the injection. The bleeding time measured at 30 min after ASA administration was significantly prolonged on the average by 70 s, 144 s and 211 s after 25 mg, 50 mg and 100 mg of ASA, respectively. Minor, but significant changes were found in tissue plasminogen activator antigen and in plasminogen activator inhibitor within the first hour after injection of low dose ASA, but similar changes were found after injection of saline. No change in tissue plasminogen activator activity was found. We conclude, that intravenous administration of low dose ASA is safe and easy, and that almost immediate, complete blockage of serum thromboxane B2 synthesis can be obtained after a single intravenous bolus injection of 100 mg.